Pengaruh Green Accounting, Good Corporate Governance (GCG), Ukuran Perusahaan dan Corporate Sosial Responsibility (CSR) Terhadap Kinerja Keuangan - Wulan Dari; Jasmina Syafei; Febri Delmi Yetti (Al-Manar Journal of Accountancy and Business Studies, 2025)
This study aims to examine the effect of green accounting, which includes environmental performance and environmental costs, as well as the implementation of Good Corporate Governance (GCG), represented by managerial and institutional ownership, plus company size and Corporate Social Responsibility (CSR) on financial performance in energy sector companies listed on the Indonesia Stock Exchange, during 2022-2024. The sample used in this study was 66 companies selected using a purposive sampling technique. The data analysis process was implemented through classical assumption tests and hypothesis testing using panel data regression methods supported by eViews version 12 software. The research findings indicate that environmental costs have a significant negative effect on financial performance, while managerial ownership, institutional ownership, and CSR exhibit a significant positive effect on financial performance. On the other hand, environmental performance and company size were not found to have a significant effect. Simultaneously, these variables explained 41.81% of the variation in financial performance, while the remaining 58.19% was estimated to be influenced by other factors not included in this study.